DESAIN OPTIMAL TERAS SMALL MODULAR MOLTEN SALT REACTOR (SM-MSR) SEBAGAI SISTROPULSI KAPAL PERANG EM P - Cahyo Ridho Prabudi; Sovian Aritonang; Topan Setiadipura (POLITALA PRESS, 2023)
Utilizing a nuclear propulsion system as a source of propulsion is one method for extending the durability of warships. Compared to using natural oil, using nuclear energy as a propulsion system offers a high effectiveness value. The Molten Salt Reactor illustrates a reactor design that can be utilized on warships (MSR). The current MSR is still quite big. Therefore in this research, an optimal design of the Small Modular Molten Salt Reactor (SM-MSR) core will be adapted to the surface area of ​​a warship. From the simulation and optimization carried out with the MCNP software, the parameter used as a reference is criticality. The optimal fuel material composition is 1% Li and 2% U-235, with an optimal design geometry having a cell core pin radius of 0.8 cm, a pin cell blanket radius of 2.6 cm, and a core height of 160 cm. The initial design of the SM-MSR in this study had a negative coefficient of void reactivity.